Penerapan Teknik Marmet Guna Memperlancar Pengeluaran ASI - Marshanda Qisty Prabasari; Septi Tri Aksari; Norif Didik Nur Imanah; Ellyzabeth Sukmawati (STIKes Ibnu Sina Ajibarang, 2023)
Ineffective breastfeeding if not immediately handled can cause problems such as swollen breasts, nipple blisters, and mastitis in mothers. To prevent this, midwives play a role in overcoming the problem of breast milk that is not smooth, one of which is by providing complementary care in the form of the marmet technique. This study aims to determine the effect of marmet technique on the smoothness of breast milk production. This research is a qualitative research with case studies with data sources and data types using primary data obtained from interviews, examinations, and observations and secondary data obtained from relevant sources. The implementation technique was carried out on Mrs. T by providing the marmet technique with a duration of approximately 20 minutes a day and conducting an evaluation after administration with the results known to have an effect on the smoothness of breast milk production.